Pendekatan Pragmatik untuk Menganalisis Novel Dokumenter Nothing but the Truth karya Avi - Fauziah, Hanny (Kementerian Sekretariat Negara Republik Indonesia, 2019)
The background of the study is a daily problem representing the events at school. There are rules implemented by school officers which must be obeyed by all school staffs, including students. However, there is a student who still disobeyed the rules. The reason why he does it, is he may not be getting enough attention from his parents and also teachers. This may be due to his parents are preoccupied with their jobs. Therefore, the student tries to seek attention from external factors, for example, from his school as his second home. Apparently, it generates a conflict between a student and their school, especially teachers.The characters involved in the conflict, are teachers, student, reporters, broadcasters, and the members of the school board. But, it will be limited, related to the theme, such as teachers, students, and some outsiders. The aims of this research are to find what the presumptions of the conflict is represented in the documentary novel Nothing But the Truth and to indicate the implications of the student who breaks the conflict by using a pragmatic approach. By using this approach, there are two ways in analyzing the data, presumptions and conversational implicatures. The findings shows us that the presumptions of the conflict happened in the novel indicate that there are feeling of bore and loneliness of the student because he gets less attention from his parents. It may happen since his parents are busy with their jobs. So, the student tries to get attention from school. While, the implications of the story of the novel are the school gets bad image from public and the student gets pay more attention from his parents by transferring him to another school which has an appropriate rule with his willing. Keywords : rules, conversational implicature, conflict, presumption, and documentary novel.